2020
DOI: 10.2478/prilozi-2020-0035
|View full text |Cite
|
Sign up to set email alerts
|

Results of Arthroscopic Treatment of Chronic Patellar Tendinopathy

Abstract: Background: The surgical treatment of chronic patellar tendinopathy could be open or arthroscopic. A general agreement on the best surgical treatment option is still lacking.Purpose: The aim of our study was to evaluate the clinical results after a minimally invasive arthroscopic treatment of chronic patellar tendinopathy including a resection of the lower patellar pole.Methods: The study included 14 patients with a mean age of 26 years and chronic patellar tendinopathy refractory to non-operative treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Moreover, decortication at the distal pole of the patella has been previously described to maximize healing potential 9 . Both surgeries give satisfactory results with success rate of more than 77% and arthroscopic surgery is associated with fewer complications, faster return to preinjury level of sport activities, and a non-significant higher success rate 4 . A review of 21 studies showed no significant differences regarding return to sports and surgical success rates between arthroscopic and open procedures 9 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, decortication at the distal pole of the patella has been previously described to maximize healing potential 9 . Both surgeries give satisfactory results with success rate of more than 77% and arthroscopic surgery is associated with fewer complications, faster return to preinjury level of sport activities, and a non-significant higher success rate 4 . A review of 21 studies showed no significant differences regarding return to sports and surgical success rates between arthroscopic and open procedures 9 .…”
Section: Discussionmentioning
confidence: 97%
“…The application of PRP has been associated with tendon healing and remodeling as a result of growth factors that lead to matrix production and heightened tenocyte activity. Several studies have shown symptomatic improvement and evidence of improvement on imaging in patients with patellar insertional tendinopathy after application of PRP 4 . The last issue that is under question is the necessity of resection of the lower patellar pole during the arthroscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen studies detailed results regarding pain, most commonly reporting scores along a VAS or as a number/percentage of patients who were pain free. 14,15,18,19,22,23,25,29,31,36,37,[42][43][44][45] Three studies 23,41,43 reporting pre-and postoperative VAS pain scores (0-10) with standard deviations had an average reduction in VAS postoperatively of 5.10 (95% CI: 4.52-5.68, I 2 ¼ 0%) which is above the MCID of 2.0 to 3.5 (►Fig. 9).…”
Section: Pain Scoresmentioning
confidence: 99%
“…Macroscopically, surgical specimens demonstrate that pathologic tendons lose the parallel, closely packed collagen fibers with increased waviness, disordered arrangement, and separated fibers as a result of mucoid degeneration, lipid deposition, and increased matrix metalloproteinases (8). In addition, multiple studies have demonstrated increased vascularity with increased neovascularization between the associated fat pads and tendons, which may result in tissue adherence and reduced glide between these structures (9). Lastly, fusiform thickening also can develop as a result of increased water content within tendon cells undergoing apoptosis (10).…”
Section: Anatomy and Pathophysiologymentioning
confidence: 99%